Jana Mazurkiewicza mitocentryczna koncepcja osobowości - Pankalla, Andrzej (My University, 2015)
The article deals with not well known theory of personality of Polish Neojacsonist psychiatrist Jan Mazurkiewicz. It describes its scientific background, biography and basic ideas and assumptions. The accent is put here on its, based on Lévi- Bruhl’s ideas but mostly original mythocentricity in psychological perspective and description of human symbolic thinking and acting.
Keywords: Jan Mazurkiewicz; Human Symbolic Thinking and Acting; Polish Neojacsonist psychiatrist; Theory of Personality